PENGARUH DEWAN KOMISARIS, DEWAN DIREKSI, DAN KOMITE AUDIT TERHADAP KINERJA KEUANGAN PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Awaliyah, Sifa Nur; Sugiarto, Sugiarto; Faturokhman, Agus (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, Indonesia, 2023)
The purpose of this study is to analyze the effect of the board of commissioners, board of directors and audit committee on company financial performance with company size as a moderating variable. This study uses a quantitative approach method. The population in this study are all consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange in 2020-2022. Samples were taken using purposive sampling technique. The data analysis technique used are panel data regression analysis and moderated regression analysis (MRA) using Eviews 12. The results of the study show that the board of commissioners has an effect on the company's financial performance. Meanwhile, the board of directors and audit committee have no effect on the company's financial performance. Company size is able to moderate the effect of the board of commissioners on the company's financial performance. However, company size is not able to moderate the effect of the board of directors and audit committee on the company's financial performance. The implications of this research is that it can increase knowledge and understand the urgency of the board of commissioners, board of directors, audit committee, and company size as an effort to improve the company's financial performance. It is hoped that this research can be used as consideration for investors in making investment decisions.